The Cocoa Husk Waste Compost as A Waste Management Solution - Akasah, Wida; Nursa'adah; Alfi, Rahmatika; Harahap, Edy Syahputra (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Deli Serdang is one of the largest centers in North Sumatra for cocoa commodities. Cocoa is strong life support for residents in Candi Rejo Village, Sibiru-Biru District, Deli Serdang Regency, especially for residents in the Pendawa Farmer Group. The abundance of cocoa harvest also causes an increase in the amount of cocoa husk waste. Still, some of the problems that arise cannot be overcome due to the limitations of science and technology. Until now, the abundant cocoa husk waste has just been piled up without any efficient processing. With training and socialization on making compost made from cocoa husk waste effectively and efficiently, the community and farmers in the Pendawa Farmer Group have increased their knowledge and ability to utilize cocoa shell waste as organic fertilizer independently. The use of compost made from cocoa husk waste is expected to increase soil fertility and create a bio-entrepreneurial spirit in the Pendawa Farmer Group.